IMPLEMENTASI PROGRAM INTEGRASI LAYANAN PRIMER (ILP) DALAM UPAYA PENINGKATAN KESEHATAN MASYARAKAT DI INDONESIA – SYSTEMATIC REVIEW - Jannah, Putri Isriyatil; Eliana, Desy; Anindya, Fauzia Liesly; Trisasri, Ruri; Awaludin; Rizki, Rahmat Kurniawan (Journal of Health Service Management, 2026)
Background: Primary health care plays a key role in ensuring the achievement of Universal Health Coverage (UHC), which is a main goal in the global health system. As one effort to strengthen primary health care services, the Indonesian government launched the Integrated Primary Care (IPC) Program (Program Integrasi Layanan Primer - ILP). Objective: This study aims to determine and analyze the implementation of the ILP program as an effort to improve public health in Indonesia. Methods: Literature searches were conducted using the Google Scholar databases, using the keywords: "primary care integration," "effectiveness of the IPC Program," "Puskesmas," and "constraints of the IPC Program." Results: The literature search process applied clear inclusion and exclusion criteria to obtain relevant literature. Based on the six articles obtained using the PRISMA method, the implementation of the Integrated Primary Care (IPC) Program (ILP) at the Puskesmas plays a vital role in improving public health status. Conclusions: Collaboration among policymakers, village governments, health workers, and health cadres is a key point in the success of the IPC Program.